Temporally increasing light intensity produces similar lettuce growth more efficiently than fixed high light - Kang, Iro; Ding, Sarah; Meng, Qingwu (Frontiers in Plant Science, 2026)
Sole-source light-emitting diode (LED) lighting is essential in growth chambers, indoor farms, and spaceflight settings. Although lettuce (Lactuca sativa) is typically grown under fixed photosynthetic photon flux densities (PPFDs), dimmable LEDs enable dynamic lighting strategies that may improve light use efficiency. However, plant responses to temporally varying PPFDs remain insufficiently characterized. An indoor experiment was conducted to determine how fixed PPFDs and temporal PPFD alternations influenced growth, morphology, and pigmentation of red-leaf lettuce ‘Rouxai’. From day 0 to 28, we grew lettuce hydroponically at 21–23 °C air temperature and 18%–27% relative humidity under six lighting treatments, including two fixed PPFDs of 150 and 350 µmol m–2 s–1 and four temporal PPFD alternations with increasing PPFDs (150→250→250, 150→350→350, 250→250→350, and 250→350→350 µmol m–2 s–1) over three phases [lag phase (days 0–11)→exponential phase (days 11–25)→finish phase (days 25–28)]. All treatments had the same light spectrum (50% warm white + 50% red) and 24-h photoperiod. Increasing the fixed PPFD from 150 to 350 µmol m–2 s–1 increased seedling shoot fresh and dry mass by 69% and 84%, respectively, leaf number from 4 to 5, leaf width by 22%, chlorophyll concentration index by 15%, and red coloration, while decreasing leaf length by 11%. Similarly, for mature plants, increasing the fixed PPFD from 150 to 350 µmol m–2 s–1 increased shoot fresh and dry mass by 66% and 70%, respectively, leaf number by 23%, leaf width by 11%, and chlorophyll concentration index by 37%, while decreasing light use efficiency by 27%–29%. Compared to the fixed 350 treatment, the 250→250→350 and 250→350→350 alternations resulted in similar biomass, morphology, and chlorophyll concentration. However, the 250→250→350 alternation had 23%–31% higher light use efficiency than the fixed 350 treatment. Increasing the total light integral from 363 to 847 mol m–2 increased shoot fresh and dry mass but decreased light use efficiency. In conclusion, a temporal light intensity alternation produces comparably high biomass in lettuce more efficiently than fixed high light.